Collegiate male athletes exhibit conditions of the Male Athlete Triad - Moris, J. M.; Olendorff, S. A.; Zajac, C. M.; Fernandez-del-Valle, M.; Webb, B. L.; Zuercher, J. L.; Smith, B. K.; Tucker, K. R.; Guilford, B. L. (Applied Physiology, Nutrition, and Metabolism, 2022)
The primary purpose of this study was to determine prevalence of the Male Athlete Triad (MAT) conditions: low energy availability (EA), low bone mineral density (BMD), and low testosterone in male collegiate athletes from different sports. Participants included 44 collegiate male athletes (age, 20.4 ± 0.2 years; body mass index, 25.3 ± 1.3 kg/m2) from 7 sports (cross country, soccer, basketball, wrestling, track, golf, and baseball). Resting metabolic rate, 3-day food intake, 7-day exercise energy expenditure, body composition, and reproductive and metabolic hormones were assessed. Of the total participants, 15% had low EA, 0% had low BMD, 28% had low total testosterone (TT), and 80% had low calculated free testosterone (cFT). There were no significant correlations between EA, BMD, TT, and cFT. Insulin and sex hormone binding globulin (SHBG) were below and on the upper end of the reference range for healthy male adults, respectively. Insulin was negatively correlated with total (r = -0.330, p = 0.043) and lumbar spine BMD z-scores (r = -0.413, p = 0.010). Low TT and low cFT were the most prevalent MAT conditions among all athletes. Further research should investigate the relationship between insulin and SHBG and the role of these hormones in the MAT. Novelty: • Assessment of energy availability alone is not sufficient to identify physiological disturbances in collegiate male athletes. • Low total and/or free testosterone may be present in some collegiate male athletes, regardless of BMD status. • Low insulin and high SHBG concentration may portray the presence of conditions of the MAT in male collegiate athletes.